The influence of compensation and motivation on the performance of civil servants at The Population and Civil Registry Office of Bandung District - Konjala, Wafda Qinthara; Wulansari, Puspita (Goodwood Publishing, 2025)
Purpose: This study aims to examine the influence of compensation and motivation on employee performance at the Population and Civil Registration Service of Bandung Regency. Method: A quantitative approach was applied using descriptive analysis and SEM-PLS to test variable relationships. The population consisted of employees of the agency, and 60 respondents were selected using a Simple Probability sampling technique. The independent variables were compensation and motivation, and employee performance was the dependent variable. Results: The findings revealed that compensation has a positive but insignificant effect on performance, while motivation shows a significant positive effect. When combined, compensation and motivation significantly improved performance. This highlights that fair compensation and increased motivation strategies play a key role in enhancing productivity and creating a supportive work environment. Conclusion: This study concludes that motivation is a stronger driver of performance than compensation alone. However, integrating both financial and motivational strategies produces a synergistic effect that supports sustainable improvement in employee performance. Limitation: The research was limited to a small sample within one government institution and focused only on two independent variables, thus reducing generalizability and excluding other potential factors, such as leadership or organizational culture. Contribution: This study enriches the public sector HR literature by emphasizing the complementary role of compensation and motivation in shaping performance and offering practical recommendations for designing balanced human resource strategies in government institutions.